COMPREHENDING LOOPS IN A PROCESS FUNCTIONAL PROGRAMMING LANGUAGE - Kollár, Ján (Computing and Informatics, 2012)
In this paper the implementation of loops in PFL - a process functional programming language is presented. The uniform conception of functions and processes in PFL makes possible to implement loops in a way similar to list comprehensions. Using process functional paradigm we will show, how the imperative loops are expressed more concisely in a purely functional manner preserving the run-time efficiency.